Academic-practice Partnership for Operating Room Nursing - Riddell, Thelma; Brar, Sukhi; Burnett, Karen; Webb, Kristen; Oudshoorn, Abe (Operating Room Nurses Association of Canada Journal, 2019)
Most schools of nursing have eliminated preparation for OR nursing from their curricula, as baccalaureate education focuses on the preparation of generalists. This article presents the program design, implementation, and overall experience of one academic-practice collaboration, in providing specialized training within a generalist undergraduate nursing program.